Performance Studies On SAG Mill In The Processing Of Gold Ore At The Hutti Gold Mines Company Limited - Gurubasayya Swamy (International Mineral Processing Congress, 2012)
This paper presents the performance study of sag mill in the processing of gold ore. Deterioting ore grade and high demand of metals has tremendously influenced the SAG mills. Today?s high capacity Semi-autogenous grinding (SAG) mills expand vast amounts of energy and in doing so consume tons of shell liners and steel balls, while processing ore. Semi-autogenous (SAG) mill performance is influenced by ball charge, feed properties, shell, grate, and pulp lifter design. In the performance study of SAG mill, based on the results obtained it can be observed that SAG mill performed better at feed size +4 inch and grinding media consumption 0.90kg/mt. In the present study the effect of crusher bypass on SAG mill performance, an immediate drop of throughput ranging from 10-20tph is observed. Keywords: sag mill, pulp lifters, grinding media, energy, consumption, throughput